Sickness rate and disability resulting from diseases of the nervous system: leading factors and ways of prevention. - A. G. Kyrychenko (Medičnì Perspektivi, 2013)
Over the past 10 years the total number of patients with diseases of the nervous system in Europe makes up 127,200,000 people, that is almost 25,8 % of the population have neurological pathology. Currently in Ukraine 1 654 875 patients with different neurological disorders are registered, in 78 % of cases disability develops which substantially worsens quality of life. By the assessment of WHO in 2012, more than 1 billion people are disabiled (15 % of the world population), of them – 2,8 million people are in Ukraine. Nervous diseases and their consequences will occupy the leading cause of disability among able-bodied population before 2020. The socio-economic aspect of the problem lies in the fact that by indices of person-years of life (index DALY) WHO evaluates disability as the global burden of diseases for the society, and most of the authors consider prevention of disability as the most economically expedient medical intervention. On this basis state Program «Health 2020: Ukrainian dimension» was approved considering new statutes of the new European politics, international experience on prevention of diseases and disability.